A Few Remarks on Legal Translation and Intercultural Encounters - Witczak-Plisiecka, Iwona (Research in Language, 2020)
The text offers comments on legal translation and its special nature. It is argued that legal translation is much different from other types of specialised translations. Unlike the language of engineering or medicine, legal language does not only refer to the related specialised practice, i.e. the law, but constitutes legal reality, being at the same time an instrument with which legal disputes are resolved. In the context of translation, legal language is particularly challenging as the process of finding equivalence is not restricted to interlinguistic level, but invites both intralinguistic and intersemiotic considerations. Moving not only between different natural languages, but also between different legal cultures, legal translators have to face problems that can often be naturally found in intercultural communication.